PERKAWINAN ENDOGAMI PERSPEKTIF HUKUM ADAT DAN HUKUM ISLAM (STUDI TERHADAP MASYARAKAT BUGIS BONE) - Nenni Rachman (Institut Agama Islam Negeri Bone, 2020)
AbstractThere are three traditional marriage system, namely: endogamy, exogamy, and eleuterogami. The Bugis Bone included into the system of marriage endogamy means that a man should marry a woman who has a relationship with a cousin, both cousins once, twice cousin, and cousin three times. According to custom Bugis Bone, marriage endogamy (Siala Massapposiseng) that occurs in the Bugis Bone is an ideal marriage, marriage according to Islam while this is not an ideal marriage. However, marriage is permissible as long as there is no prohibition in the passage, both the Quran and al-Hadith. This study aims to determine the factors behind marital endogamy and the impact of the marriage. The method used in this research is a field research dealing directly with the public, in order to obtain clear data and data collection techniques of interviews and documentation. The results showed that there were several factors behind the retaining endogamous marriage among others: purity of lineage, wealth care, and spatial orientation (territorial). In practice, endogamous marriage have an impact, especially for perpetrators of endogamy itself among others: strengthens kinship, wealth preservation or heritage, and the impact of physical or mental disability in the offspring